Pengaruh Berat Bayi Lahir Rendah dengan Kejadian Stunting Anak 6–36 Bulan - Finda Wijayanti; Herry Garna; Buti Azfiani (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. Stunting is a condition of malnutrition in childhood that causes children to grow smaller than their age. The incidence of stunting according to data obtained from the World Health Organization (WHO) 2021 in the world reached 22% or 149.2 million in 2020. Basic Health Research Data (Riskesdas) 2018 stated that the prevalence of Indonesian children experiencing stunting was 30.8% or around 7 million toddlers. The prevalence of children experiencing stunting based on the SSGI in Bandung City reached 19.4%. Low birth weight is one of the factors causing stunting. The aim of the research is to analyze the influence of low birth weight on the incidence of stunting in children aged 6–36 months at the Babakan Ciparay District Health Center in 2023. This research uses a non-probability sampling technique with 105 research subjects at the Babakan Ciparay District Health Center during February–November. 2023. The method in this research uses observational analytics with a case control research design. The results of research conducted on children at the Babakan Ciparay District Health Center showed that 33% of children were stunted and 12% had low birth weight babies. Abstrak. Stunting merupakan keadaan malnutrisi pada masaa kanak-kanak yang menyebabkan anak tumbuh lebih kecil dari usianya. Kejadian stunting menurut data yang didapatkan dari World Health Organization (WHO) 2021 di dunia mencapai 22% atau 149,2 juta pada tahun 2020. Data Riset Kesehatan Dasar (Riskesdas) 2018 menyatakan prevalensi anak Indonesia mengalami stunting sebesar 30,8% atau sekitar 7 juta balita. Prevalensi anak yang mengalami stunting berdasarkan SSGI di Kota Bandung mencapai 19,4%. Berat bayi lahir rendah menjadi salah satu faktor penyebab kejadian stunting. Tujuan penelitian menganalisis pengaruh berat bayi lahir rendah dengan kejadian stunting pada anak usia 6–36 bulan di Puskesmas Kecamatan Babakan Ciparay pada tahun 2023. Penelitian ini menggunakan teknik pemilihan sampel non probability sampling dengan 105 orang subjek penelitian di Puskesmas Kecamatan Babakan Ciparay selama Februari–November 2023. Metode pada penelitian ini menggunakan analitik observasional dengan rancangan penelitian case control. Hasil penelitian yang dilakukan terhadap anak di Puskesmas Kecamatan Babakan Ciparay terdapat anak stunting sebanyak 33% dan berat bayi lahir rendah 12%.